Oralidade na escola: um trabalho com o gênero oral debate regrado em oficinas de língua portuguesa - Vitorino, Luane Guerra (2018)
This dissertation – linked to the Postgraduate Program in Languages, in the Linguistic Studies area, from the Federal University of Santa Maria (UFSM) – aims to investigate the teaching and learning processes of the public debate genre, based on a work developed with High School students. The theoretical framework is based on the notion of language as a form of social interaction proposed by Bakhtin/ Volochinov (2014); on the teaching social-interactionist perspective, advocated by Vigotski (1987; 2007),as well as the theories related to oral genres and the debate genre, such as Travaglia (2007; 2017), Bentes (2010), Neves (2001) and Dolz and Schneuwly (2004).The workshops methodology is anchored in action research, proposed by Thiollent (1985) and Tripp (2005), which enables interaction between the research subjects and the researcher. The workshops methodology is grounded in action research, proposed by Thiollent (1985) and Tripp (2005), which enables interaction between the research subjects and the researcher. The research was carried out weekly in workshops of oral textual production, between October and December in 2017, with volunteer students of the 2nd year of High School in a State School from Santa Maria (RS, Brazil).The corpus analysis is based on three criteria presented by Travaglia (2007; 2017): compositional structure, socio communicative objectives/function and linguistic surface characteristics. With this research, we have found benefits in relation to the qualification of oral textual productions, focusing on the argumentative competence of the students, especially regarding the quality of the arguments and the appropriation in relation to the oral public debate genre.